"Olśnienie w niespokojnym niebie wieszcza". "Pan Tadeusz" Ryszarda Ordyńskiego (1928) - perspektywa wirtualnego odbiorcy = "Illumination in the turbulent sky of the poet". Ryszard Ordyński's film "Sir Thaddeus" (1928) - a virtual viewer's perspective - Kopczyński, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The discovery in 2006 and a digital reconstruction of successive fragments of a copy of the 1928 film "Pan Tadeusz" ("Sir Thaddeus"), a silent film adaption of Adam Mickiewicz's epic poem of 1834 created for the 10th anniversary of independence, will give audiences a chance to examine the adaptation's premises once more.
Keywords: "Pan Tadeusz"; adaptacja filmowa; Ordyński, Ryszard Stanisław Kazimierz (1878-1953)